Reinterpretasi Ḥadīts Perintah Memukul Anak - Ferra Dwi Jayanti (Refleksi: Jurnal Kajian Agama dan Filsafat, 2016)
This article offers a new interpretation of Ḥadīth that allows parents to hit and accomplishes violence towards their children if the children do not do the prayer. It shows that the word ḍaraba (hit) in the prayer order does not mean violence, but education by wise and gentle. Therefore the word ḍaraba has real and metaphorical meaning. While the order for violence as stated in the Prophet Ḥadīths is connected to punishment (ḥad.) Moreover, the history proves that the Prophet never conducted violence in his life, neither to hit anybody, unless in the war and punishment.